(3cJGH aj JQGLe GdTjhN GdPjf dbHge GdSNGhj HGdTGe heUQs - (3GdSNGhj , TeS GdOjf eMeO Hf YHO GdQMef Hf eMeO GdSNGhj, GdSNGhj,J (B902 (3g` s
(3ChdgG (B:s
(3hHYO, aEf HYV GdCUMGH SCdfj Cf CcJH dg JQGLe GdTjhN GdPjf ELJeYJ Hge aj MdJj Edi GdHdGO GdeUQjI hGdTGejI s
(3BNQgG (B:s
(3jfJgj CKfGA JQLeI GdMGaX GHf MLQ GdYSbdGfj s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B9s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B194 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B150s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B339 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs